Integration of AI-Powered Wearable Biosensors for Continuous Health Monitoring: A New Frontier in Medical Instrumentation Engineering - Sakr, Zahraa Aad Kazem; diwan, Ahmed hatem khorsheed; yassin, Ahmed wadullah azeez; Khader, Ahmed natheer yahya; Mahmoud, Hussein Mohamed Thamer; Ali, Abdulrahmn khalid Mahmoud Mohamad (American Journal of Biomedicine and Pharmacy, 2025)
Wearable biosensors are innovative portable devices, typically wireless, designed to be worn on the human body to acquire a wide range of physiological and biochemical data. These advanced sensors automate the continuous tracking of vital signs, and they provide the capability for real-time health status reporting, which includes options for remote monitoring and alerting healthcare professionals when necessary. The integration of wearable biosensors with advanced electronic technologies, coupled with AI-driven machine learning methods, is paving the way for groundbreaking developments in early-stage disease surveillance, intensive symptom tracking, and enhanced preventative healthcare measures. Ordinary consumer electronics, such as mobile phones, smart watches, and fitness bands, now often incorporate state-of-the-art biosensing components that are capable of measuring various indicators, including heart rate, blood oxygen levels, skin temperature, calories burned, and steps taken throughout the day. The concept of continuous health monitoring represents a transformative frontier in the dynamic field of medical instrumentation engineering, providing individuals with unprecedented insights into their health and well-being, thereby fundamentally changing the landscape of personal healthcare management.